Effects of autologous platelet-rich plasma in promoting endometrial thickness on patients with thin endometrium following IVF - Gita Pratama; Elizabeth Agustina; Atika Mahira Yanfaunnas; Mila Maidarti; Achmad Kemal Harzif; R. Muharam; Budi Wiweko (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS